2021
DOI: 10.3390/nano11041030
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Magnetic Micro- and Nanospheres and the Effect of Applied Magnetic Fields

Abstract: The impact of in-plane and perpendicular magnetic fields on the spatial arrangement of superparamagnetic nanospheres is explored. We utilize nanosphere self-organization methods like Spin Coating and Drop-Casting in the presence of magnetic fields. In this way, the additional parameter of the long range magnetic dipolar interactions is introduced to the competing nanosphere–surface and nanosphere–nanosphere interactions, which control order and agglomeration. We present a comparative analysis of the self-assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In fact, many attempts to design and modulate the structure of organic nanomaterials have been made by scientists worldwide, [32][33][34][35] especially aer the successful reporting of molecular self-assembly strategies driven by weak intermolecular interactions (including van der Waals forces, pp interactions, hydrogen bonds, and CH-p interactions). In the early stages, our research group and other research groups demonstrated abundant low-dimensional micro/ nanocrystals [36][37][38][39] (e.g., 0D nanoparticles, 1D nanowires, nanotubes, and 2D nanosheets) prepared by reprecipitation, 40,41 solution drop-casting, 42,43 solvent evaporation method, 44,45 etc., which provide novel device structures and resonator types for organic photonic devices (Fig. 1a-c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many attempts to design and modulate the structure of organic nanomaterials have been made by scientists worldwide, [32][33][34][35] especially aer the successful reporting of molecular self-assembly strategies driven by weak intermolecular interactions (including van der Waals forces, pp interactions, hydrogen bonds, and CH-p interactions). In the early stages, our research group and other research groups demonstrated abundant low-dimensional micro/ nanocrystals [36][37][38][39] (e.g., 0D nanoparticles, 1D nanowires, nanotubes, and 2D nanosheets) prepared by reprecipitation, 40,41 solution drop-casting, 42,43 solvent evaporation method, 44,45 etc., which provide novel device structures and resonator types for organic photonic devices (Fig. 1a-c).…”
Section: Introductionmentioning
confidence: 99%
“…In the early stages, our research group and other research groups demonstrated abundant low-dimensional micro/nanocrystals 36–39 ( e.g. , 0D nanoparticles, 1D nanowires, nanotubes, and 2D nanosheets) prepared by reprecipitation, 40,41 solution drop-casting, 42,43 solvent evaporation method, 44,45 etc. , which provide novel device structures and resonator types for organic photonic devices (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly is an essential fabrication technology to precisely manipulate nanomaterials to form highly ordered monolayer or multilayer films, which attracted much attention in the past decade. The process temperature of self-assembly is much lower than the micromachining process, normally at room temperature, which makes it compatible with polymeric materials fabrication , and friendly to flexible and wearable electronics. The universality of self-assembly in diverse material domains has been demonstrated, such as noble metals, , magnetic metals, , semiconductors, oxidation, and polymers. , However, microscale patterning is always a critical challenge to restrict the further and wider application of self-assembly. Self-assembly-based irregular micropatterns could be obtained through unusual methods, such as bubble and droplet templates.…”
Section: Introductionmentioning
confidence: 99%
“…Geometric regulations like adjusting anisotropy, the length to diameter ratio, and assembling are efficient strategies to fabricate magnetic materials with distinctive morphology and size, which make it feasible to obtain the stable combination of multiple vortex domains. Particularly, when assembled with various dimensional building blocks such as nanoparticles, nanowires, , nanosheets, , and nanospheres, , the magnetic structures could achieve the synergistic effect from different units with spatial confinement and the pluralism of mechanisms. To date, there are plenty of synthetic strategies to assemble monodisperse magnetic building blocks.…”
Section: Introductionmentioning
confidence: 99%